2015
DOI: 10.1371/journal.pone.0134666
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Sevoflurane Postconditioning against Cardiac Ischemia/Reperfusion Injury via Ameliorating Mitochondrial Impairment, Oxidative Stress and Rescuing Autophagic Clearance

Abstract: Background and PurposeMyocardial infarction leads to heart failure. Autophagy is excessively activated in myocardial ischemia/reperfusion (I/R) in rats. The aim of this study is to investigate whether the protection of sevoflurane postconditioning (SPC) in myocardial I/R is through restored impaired autophagic flux.MethodsExcept for the sham control (SHAM) group, each rat underwent 30 min occlusion of the left anterior descending coronary (LAD) followed by 2 h reperfusion. Cardiac infarction was determined by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
70
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(75 citation statements)
references
References 55 publications
(76 reference statements)
5
70
0
Order By: Relevance
“…It is widely known that in endogenous protection mechanisms, PC 16 and PostC 17 increase cell survival pathways, at least partially, by decreasing the oxidative stress damage after I/R injury [23][24][25][26]. Therefore it is interesting to review the role of the Trx system in the endogenous protection mechanisms.…”
Section: Thioredoxin Effects On Cardioprotection Mechanisms Ischemicmentioning
confidence: 99%
“…It is widely known that in endogenous protection mechanisms, PC 16 and PostC 17 increase cell survival pathways, at least partially, by decreasing the oxidative stress damage after I/R injury [23][24][25][26]. Therefore it is interesting to review the role of the Trx system in the endogenous protection mechanisms.…”
Section: Thioredoxin Effects On Cardioprotection Mechanisms Ischemicmentioning
confidence: 99%
“…Sevoflurane is a widely used volatile anesthetic in cardiac surgery. It is demonstrated that sevoflurane postconditioning (SPC) limits myocardial infarct size and reduces mortality in both animal models and clinical practice [3][4][5][6]. Similarly, remote ischemic preconditioning (RIPC) by applying several cycles of ischemia and reperfusion in distant tissues also presents the protective effect.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the combined effect is not tested in rat myocardial ischemia/reperfusion (I/R) model. Previous studies suggest that a variety of mechanisms may be responsible for the cardioprotection of SPC and RIPC against I/R injury, including the Reperfusion Injury Salvage Kinase pathway (RISK pathway) inhibition [8], preventing mitochondrial permeability transition pore (mPTP) from opening [9], decreasing intracellular reactive oxygen species (ROS) levels [10], and regulating the activation of autophagy or the process of autophagic flux [4,11]. However, the precise mechanisms remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies suggest that sevoflurane exposure induces neuroapoptosis through caspase-3 activation and increase in β-amyloid protein levels in vivo and in vitro, while other studies suggest a neuroprotective effect [29] [30] [31]. This discrepancy could be explained by differences in cells lines, exposure time to anesthesia and concentration of inhalation agents.…”
Section: Discussionmentioning
confidence: 99%